Acetylation of PHF5A Modulates Stress Responses and Colorectal Carcinogenesis through Alternative Splicing-Mediated Upregulation of KDM3A - Wang, Zhe; Yang, Xin; Liu, Cheng; Li, Xin; Zhang, Buyu; Wang, Bo; Zhang, Yu; Song, Chen; Zhang, Tianzhuo; Liu, Minghui; Liu, Boya; Ren, Mengmeng; et al. (Molecular cell, 2019)
Alternative pre-mRNA-splicing-induced post-transcriptional gene expression regulation is one of the pathways for tumors maintaining proliferation rates accompanying the malignant phenotype under stress. Here, we uncover a list of hyperacetylated proteins in the context of acutely reduced Acetyl-CoA levels under nutrient starvation. PHF5A, a component of U2 snRNPs, can be acetylated at lysine 29 in response to multiple cellular stresses, which is dependent on p300. PHF5A acetylation strengthens the interaction among U2 snRNPs and affects global pre-mRNA splicing pattern and extensive gene expression. PHF5A hyperacetylation-induced alternative splicing stabilizes KDM3A mRNA and promotes its protein expression. Pathologically, PHF5A K29 hyperacetylation and KDM3A upregulation axis are correlated with poor prognosis of colon cancer. Our findings uncover a mechanism of an anti-stress pathway through which acetylation on PHF5A promotes the cancer cells’ capacity for stress resistance and consequently contributes to colon carcinogenesis. [Display omitted] •Quantitative acetylomics reveals hyperacetylated proteins upon nutrition starvation•Multiple cellular stresses result in p300-dependent PHF5A K29 acetylation•PHF5A K29 acetylation enhances KDM3A expression by stabilizing its mRNA•PHF5A acetylation and KDM3A upregulation predict poor prognosis in colon cancer Wang et al. uncover a list of proteins that become hyperacetylated upon nutrient starvation. p300-mediated PHF5A K29 acetylation is induced by multiple cellular stresses and affects global pre-mRNA splicing. PHF5A acetylation upregulates KDM3A expression by reducing its aberrant mRNA alternative splicing, which is positively correlated with colorectal tumorigenesis.